2018
DOI: 10.1186/s12879-018-3289-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, intensity and factors associated with soil-transmitted helminths infections among preschool-age children in Hoima district, rural western Uganda

Abstract: BackgroundOver 80% of morbidity due to soil-transmitted helminthiasis (STH) occurs in low-income countries. Children under 5 account for 20–30% of the burden in endemic areas. This study assessed the prevalence, intensity and factors associated with STH infections among preschool-age children (PSAC) in Hoima district, Uganda. The PSAC are particularly vulnerable because the chronicity of this condition usually affects their physical and mental growth and development.MethodsA cross-sectional study was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
31
12
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 46 publications
20
31
12
10
Order By: Relevance
“…The nding of the current review (17%) is in line with ndings from South America (15.6%), studies conducted in Amhara region, Ethiopia (16.8%) and the overall burden in Sub-Saharan African countries (15%) [122]. However, it was lower than results from Nigeria (44.6%), Rwanda (38.6%), Uganda (43.5%) [123], Kenya (24.3%) [124] and previous estimate in Ethiopia (37%). The observed differences might be due variation in some factors putting population at risk of acquiring STHs such as geographical variations, life style of the community, soil humidity and exposure to contaminated environments..…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The nding of the current review (17%) is in line with ndings from South America (15.6%), studies conducted in Amhara region, Ethiopia (16.8%) and the overall burden in Sub-Saharan African countries (15%) [122]. However, it was lower than results from Nigeria (44.6%), Rwanda (38.6%), Uganda (43.5%) [123], Kenya (24.3%) [124] and previous estimate in Ethiopia (37%). The observed differences might be due variation in some factors putting population at risk of acquiring STHs such as geographical variations, life style of the community, soil humidity and exposure to contaminated environments..…”
Section: Discussionsupporting
confidence: 84%
“…The nding of thee current review showed that the prevalence of hookworms was 12% indicating that the current nding is lower than others studies conducted in Nigeria (32.7%) [114] and Uganda (18.5%) [123]. However, it was higher than studies conducted in Kenya (0.4%) [124], Rawanda (1.8%) [126]and Cameroon (3.9%) [127].…”
Section: Discussionmentioning
confidence: 52%
“…Ivermectin is not approved in children weighing < 15 kg; hence, this age group is excluded from official treatment programs. The drug has been widely used off‐label in a single‐dose administration for various indications, and given that young children may have high prevalence of helminth infections and scabies and serve as an important reservoir of Plasmodium , there is a need to build an evidence base to determine safe and effective ivermectin doses in the pediatric population. Ivermectin pharmacokinetics (PK) in adults has been described in a small number of healthy volunteers and patients with onchocerciasis, Trichuris trichiura infection, or malaria .…”
mentioning
confidence: 99%
“…10,11 Ivermectin is not approved in children weighing < 15 kg; hence, this age group is excluded from official treatment programs. The drug has been widely used off-label in a single-dose administration for various indications, and given that young children may have high prevalence of helminth infections [12][13][14][15] and scabies 16,17 and serve as an important reservoir of Plasmodium, 18,19 there is a need to build an evidence base to determine safe and effective ivermectin doses in the Study Highlights WHAT IS THE CURRENT KNOWLEDGE ON THE TOPIC? ✔ Ivermectin is widely used to treat various helminth infections and may be used in malaria vector control, but doses that produce consistent exposure coverage in children of various ages and adults are still unknown.…”
mentioning
confidence: 99%
“…Prevalensi cacing parasit pada anakanak sebesar 57,6% [6]. Anak-anak terinfeksi cacing parasit sebesar 26,5% [7]. Prevalensi cacing parasit pada anak-anak sebesar 36% [8].…”
Section: Pendahuluanunclassified